Effect of Addition of Monosodium Glutamate (MSG) on Coagulation Basin to Characteristics of Cellulose Acetate Membranes - Rofiqoh, Siti; Indarti, Dwi; Piluharto, Bambang (Jurnal ILMU DASAR, 2016)
The aim of recearch is study the effect of MSG in coagulation basin on cellulose acetat membranes properties. It was preparated by phase inversion technique. As the result showed that the higher the concentration of MSG in coagulation basin, which is character of membrane permeability coefficients and lower water flux. Dextran rejection of 11, 40, 100-200, and 500 kDa increased. The morphology analysis has shown that sub layer membranes structure with 2% MSG addition more uniform than 0,5% MSG addition.Keywords: cellulose acetat, phase inversion, MSG, coagulation basin